Climatic and socio-demographic factors stand out in Ceará cities with higher incidence of arbovirosis transmitted by Aedes aegypti (Research, Society and Development, 2022)
According to the literature, environmental, demographic and socioeconomic factors have contributed to the maintenance of high rates of dengue cases in Ceará. In addition, the introduction of viruses such as Chikungunya and Zika in 2014 worsened the endemic scenario. Thus, in view of the favourable conditions for endemics and the permanent need for new studies to understand the dynamic role of arbovirus infections in Ceará, the objective of this study was to evaluate factors related to the highest incidence of arboviroses in Ceará cities in 2021.This is a study based on data released by the Health Secretariat of the Government of the State of Ceará (SESA). Among the 184 municipalities of Ceará, the ten cities with higher and lower incidence of arboviroses transmitted by Aedes aegypti in 2021 were selected, generating two groups and, therefore, the variables population density, rainfall, temperature, human development index (HDI), education, income, infant mortality, health facility, number of doctors, availability of drinking water, sanitation and household waste collection were analyzed. The data collected were analysed in the PRIZMA programme. The results revealed that the ten municipalities with the highest incidence of cases of arbovirosis present significantly higher population concentration, average and minimum temperatures, HDI, income, infant mortality, number of health establishments, number of physicians, sanitation rate, and solid waste collection when compared with the ten municipalities with the lowest incidence. However, there was no difference between the groups when maximum temperature and rainfall were evaluated. Therefore, we suggest that agencies and secretariats related to dengue control, as well as the community intensify their actions not only during the rainy season, but also act throughout the year, since other factors contribute to the increase in cases of arbovirosis in the cities of Ceará.